Mustard Gold in the Oleninskoe Gold Deposit, Kolmozero–Voronya Greenstone Belt, Kola Peninsula, Russia - Arkadii A. Kalinin; Yevgeny E. Savchenko; Ekaterina A. Selivanova (Minerals, 2019)
The Oleninskoe intrusion-related gold–silver deposit is the first deposit in the Precambrian of the Fennoscandian Shield, where mustard gold has been identified. The mustard gold replaces küstelite with impurities of Sb and, probably, gold-bearing dyscrasite and aurostibite. The mosaic structure of the mustard gold grains is due to different orientations and sizes of pores in the matrix of noble metals. Zonation in the mustard gold grains is connected with mobilization and partial removal of silver from küstelite, corresponding enrichment of the residual matter in gold, and also with the change in the composition of the substance filling the pores. Micropores in the mustard gold are filled with iron, antimony or thallium oxides, silver chlorides, bromides, and sulfides. The formation of mustard gold with chlorides and bromides shows that halogens played an important role in the remobilization of noble metals at the stage of hypergene transformation of the Oleninskoe deposit.